Preparation and Properties of Corn Starch/Chitin Composite Films Cross-Linked by Maleic Anhydride - Yin, Peng (Polymers (Basel), 2020)
To improve the functional properties of starch-based films, chitin (CH) was prepared from shrimp shell powder and incorporated into corn starch (CS) matrix. Before blending, maleic anhydride (MA) was introduced as a cross-linker. Composite CS/MA-CH films were obtained by casting-evaporation approach. Mechanical property estimation showed that addition of 0–7 wt % MA-CH improved the tensile strength of starch films from 3.89 MPa to 9.32 MPa. Elongation at break of the films decreased with the addition of MA-CH, but the decrease was obviously reduced than previous studies. Morphology analysis revealed that MA-CH homogeneously dispersed in starch matrix and no cracks were found in the CS/MA-CH films. Incorporation of MA-CH decreased the water vapor permeability of starch films. The water uptake of the films was reduced when the dosage of MA-CH was below 5 wt %. Water contact angles of the starch films increased from 22° to 86° with 9 wt % MA-CH incorporation. Besides, the composite films showed better inhibition effect against Escherichia coli and Staphylococcus aureus than pure starch films.